CORRELATION ANALYSIS OF SEDIMENTARY ROCKS OF NOVOHRAD BLOCK (VOLYNSKY MEGABLOCK OF UKRAINIAN SHIELD) - Baran, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
There are many correlation dependencies in of Novohrad block of the ІІ order of Volynsky megablock of the Ukrainian Shield calculated by the Pierson`s method. They are associated with daylight surface of this relief, Precambrian basement, crystalline rocks and thickness of sedimentary rocks. A part of these associations reflects well known and anticipated trends and patterns in geological structure of the block surface. This is a significant inheritance of crystalline basement by surface relief, increase of sedimentary cover in basement degradation, etc. A part of established dependences is expected in total, but it is not predictable in details. For example, correlation association of thickness of sedimentary cover with thickness of separate varieties of sedimentary rocks is predictable, but the power of connections with separate varieties of deposits is unpredictable. Some dependencies, on this stage of exploration of the Ukrainian Shield surface, are completely unpredictable. These include the lowest values of linear dependence on the least common rocks with surface of Precambrian basement, crystalline rocks and thickness of sedimentary cover, compared to more common rocks, etc. Confirmation of well-known patterns by correlation method indicates objectivity of method in this application. At the same time, correlation analysis allows to reveal new tendencies, unpredictable dependencies in the structure of sedimentary deposits, which determines the necessity of their further statistic analysis.
Keywords: basement; rock; sedimentary cover; power